2007
DOI: 10.1002/em.20295
|View full text |Cite
|
Sign up to set email alerts
|

Lack of genotoxicity induced by endogenous and synthetic female sex hormones in peripheral blood cells detected by alkaline comet assay

Abstract: The etiology of hormone-induced cancers has been considered to be a combination of genotoxic and epigenetic events. Currently, the Comet assay is widely used for detecting genotoxicity because it is relatively simple, sensitive, and capable of detecting various kinds of DNA damage. The present study evaluates the genotoxic potential of endogenous and synthetic sex hormones, as detected by the Comet assay. Blood cells were obtained from 12 nonsmoking and 12 smoking women with regular menstrual cycles and from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Regarding DNA damage, several studies reported increased levels of 8-hydroxyguanine in smokers compared to nonsmokers [ 17 19 ]. However, conflicting results have been reported with comet assays to measure DNA damage related to ETS [ 20 22 ]. Hoffmann and Speit showed no significant difference in genotoxic effects in peripheral bloods cells between heavy smokers and nonsmokers [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding DNA damage, several studies reported increased levels of 8-hydroxyguanine in smokers compared to nonsmokers [ 17 19 ]. However, conflicting results have been reported with comet assays to measure DNA damage related to ETS [ 20 22 ]. Hoffmann and Speit showed no significant difference in genotoxic effects in peripheral bloods cells between heavy smokers and nonsmokers [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…8-hydroxyguanine, a biomarker of oxidative DNA damage was increased in human leukocytes, urine and lung tissue of smokers compared to nonsmokers [ 17 19 ]. However, other clinical and experimental studies showed no difference in DNA damage, assessed by the comet assay, in peripheral blood of human or rats exposed to tobacco smoke [ 20 22 ]. Likewise, plasma protein carbonyl concentration, a marker of protein oxidative damage, was increased in heavy smokers in some but not all studies [ 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that induction of homo oxygenases leads to the conversion of procarcinogenes-carcinogens [43] or by stimulation of the genetically altered pre-neoplastic cells [44]. The relationship between the carcinogens and sex hormones is not very clear, however a series of or combination of genotoxic and epigenetic changes have been reported to be associated with OC users [45]. In our earlier in vitro studies synthetic progestins have been reported to generate reactive oxygen species (ROS) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Genotoxicity assay. The comet assay was performed in duplicate to evaluate DNA damage in peripheral blood cells by following the guidelines (Singh et al 1988) with some modifications (Tice et al 1991, Braz & Salvadori 2007. Every step was carried out under indirect light.…”
Section: Methodsmentioning
confidence: 99%